Penerapan Metode Muraja'ah Dalam Meningkatkan Halafalan Al-Qur'an Siswa Di MTs DDI Kaballangang Kabupaten Pinrang - Rifky, Ahmad; Anwar, Muhammad Yunus; Wahab, Abdul; Mustamin, Mustamin; Ahmad, Ahmad (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This study evaluates the application of the muraja'ah method in improving the ability to memorize the Qur'an in class VIII.3 students at MTs DDI Kaballangang, Pinrang Regency. Muraja'ah, as a memorization repetition technique, is intended to strengthen memory of the verses of the Qur'an. Classroom action research (CAR) conducted in two cycles, including planning, implementation, observation, and reflection, showed a significant increase in students' memorization abilities. Before the application of the muraja'ah method, only 29% of students achieved the completion criteria with an average score of 65.00. After cycle I, this percentage increased to 62% (average 76.76), and at the end of cycle II it reached 91% with an average score of 85.00. In addition to academic improvements, there was also an increase in students' self-confidence, perseverance, and motivation in memorizing. Therefore, the muraja'ah method has proven effective and is recommended as a continuous learning strategy to improve students' ability to memorize the Qur'an in the Al-Qur'an Hadith subject